Optimización del sistema de explotación subterráneo en la producción eficiente del bloque 2N de la mina Telma, ubicada en el cantón Portovelo, provincia de El Oro. - Carrión Delgado, Alex Adrián (2024)
This project covers various crucial aspects of underground mining, including deposit geology, geomechanical characteristics of the rock mass, and exploitation systems. It also presents a technical and economic evaluation of the proposed optimization for the exploitation system of the 2N block. The topics addressed include topography, structural geology, geomechanical classifications, the underground mining cycle, and the production costs associated with mining. Additionally, the project provides a detailed description of the current activities within the 2N block and proposes a design to optimize the exploitation system based and proposes a design to optimize the exploitation system based on Nichol´s numerical methodology and a multi-criteria analysis. The results demonstrate the daily productivity of the 2N block both currently and under the proposed optimization. Furthermore, a technical-economic comparison is made between the costs per meter of advance and per ton of extracted mineral in both the current operations and the optimization proposal. In summary, this research aims to improve the efficiency of the exploitation of the 2N block exploitation at the Telma Mine, considering both technical and economic aspects, as well as present ore grades, to achieve more efficient and profitable production. Keywords: Exploitation systems, geological and geomechanical characteristics, technical - economic analysis